Personal Knowledge Management (PKM) pada Pengikut Akun Autobase @collegemenfess - Nanda Khaerunnisa Syafitri; Angga Hadiapurwa; Hafsah Nugraha (Pustakaloka, 2022)
Information search activities are things that are usually done by students in meeting information needs. Twitter is one of the social media that can be used as an information search engine. In Indonesia, there has been a phenomenon of using automatic fanbase (autobase) twitter which is used as one of the information search media by students, namely autobase twitter @collegemenfess. Through the @collegemenfess autobase media network, there can be an exchange of information and knowledge that can support Personal Knowledge Management. The purpose of this study is to examine how personal knowledge management is on followers of the @collegemenfess autobase account. The research method used is descriptive with a quantitative approach to 100 respondents who are followers and users of the @collegemenfess autobase account. The results of this study are that there is a very good category of assessment in the aspect of Personal Knowledge Management ability which includes the ability to retrieve information and analyze information and in a good category in the aspect of the ability to evaluate or assess information and organize information. Meanwhile, in presenting information, respondents tend to be more adept at presenting information in written than verbal.